(untitled) (International Journal of Public Health and Nursing, 2025)
Effective time management has become increasingly important for head nurses to accomplish the health care organizations’ objectives. Also, time management can help head nurses in balancing their professional and personal lives. Learning how to manage nursing time at work will reduce work stress, burnout and gain control over work. The present study is conducted to assess the effect of time management training on head nurses’ work-family conflict. A one group pretest - posttest quasi-experimental design has been conducted to achieve the aim of this study. The study was conducted at maternity hospital which affiliated to Ain-Shams University Hospitals. The subjects of the study included 40 head nurses working at mention setting. The results indicated that there was a highly statistical significant difference between pre /post, pre / follow up results regarding time management knowledge level, work-family conflict (p-value .05). The study revealed that the head nurses ‘work-family conflict reduced markedly after implementing the time management training in the intervention.